Pengaruh Media Pembelajaran Quizlet terhadap Hasil Belajar Fikih Kelas 5 - Latinisah, Nia; Susanti, Cela Petty (Paedagogie, 2026)
One important field in Islamic religious education is fiqh, which studies Islamic laws concerning human relationships with Allah and with one another. Research conducted in class V at MI Al-Kausar Ponorogo shows that student learning achievements are below the minimum competency standard. This is due to a lack of understanding among students, a learning approach dominated by lectures, and a lack of variety in learning media. As a result, students quickly become bored and inactive in class. To overcome this problem, researchers suggest using Quizlet as a learning tool that makes fiqh lessons more interactive, independent, and enjoyable for students. This study used a quantitative approach and employed a real design of a pre-test and post-test control group. Simple random sampling was used to select 51 students. Data were collected using multiple-choice tests and analysed using SPSS 25. The results of the analysis using the Mann-Whitney nonparametric test show that Ho is rejected and Ha is accepted, with a Sig (2-tailed) value of 0.011 < 0.05. Thus, the evidence shows that Quizlet is effective in improving students' understanding of Fiqh. The researcher suggests that teachers use it as a creative tool and students use it as a way to study independently.